Ultrafiltration operational conditions influence in the antibacterial activity of native and thermally treated lysozyme - de Espindola, Ariane; Miron, Simona M.; Dutournié, Patrick; Ponche, Arnaud (Comptes Rendus. Chimie, 2023)
To obtain high quality final products, biomolecules can be exposed in production lines to stress factors such as heating, stirring and multiple surfaces contact before their commercialization. These factors can induce stability and efficacy loss. In this work, the antibacterial activity of lysozyme (LSZ), a protein used as antibiotic which acts by disrupting the bacterial cell wall, was studied after two operations: heating and ultrafiltration. Antibacterial activity after extreme stress factors is expected to decrease due to conformational changes in the protein molecule. It was observed that ultrafiltration can promote an activity decrease proportional to the applied transmembrane pressure of a non-treated lysozyme. However, when a thermally treated lysozyme (90 °C) was filtered, no additional effect was observed due to the pore passage, independently of the applied pressure.